2008
DOI: 10.1038/nrc2467
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein signalling in colorectal cancer

Abstract: Much of the current understanding of colorectal cancer stems from the study of rare, inherited colorectal cancer syndromes. Mutations in the bone morphogenetic protein (BMP) pathway have been found in juvenile polyposis, an inherited polyposis syndrome that predisposes to colorectal cancer. The hamartomas that develop in these patients and in BMP pathway mutant mice have a remarkable mesenchymal component. Further evidence in mice suggests a primary role for mesenchymal loss of BMP signalling in hamartoma deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
152
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 45 publications
3
152
0
Order By: Relevance
“…The comparison of human adenoma and colorectal cancer specimens revealed the loss of active BMP signaling pathway in 9.1% and 77.7%, respectively, (Kodach et al, 2007;2008a) which correlated with tumor progression from late adenoma to early carcinoma. The most prominent finding was the loss of BMPRII and Smad4 expression in colorectal carcinoma (Hardwick et al, 2008;Kodach et al, 2007;2008a) which was confirmed by similar findings in sporadic colorectal carcinoma. The loss of BMPRII expression was strictly correlated with microsatellite instability (Kodach et al, 2008b).…”
Section: Bmps and Their Pathway In Gastrointestinal Cancerssupporting
confidence: 69%
See 1 more Smart Citation
“…The comparison of human adenoma and colorectal cancer specimens revealed the loss of active BMP signaling pathway in 9.1% and 77.7%, respectively, (Kodach et al, 2007;2008a) which correlated with tumor progression from late adenoma to early carcinoma. The most prominent finding was the loss of BMPRII and Smad4 expression in colorectal carcinoma (Hardwick et al, 2008;Kodach et al, 2007;2008a) which was confirmed by similar findings in sporadic colorectal carcinoma. The loss of BMPRII expression was strictly correlated with microsatellite instability (Kodach et al, 2008b).…”
Section: Bmps and Their Pathway In Gastrointestinal Cancerssupporting
confidence: 69%
“…Transgenic mice which overexpressed the BMP anatagonist noggin or mice with conditional inacativation of BMPRIA which led to disruption of both epithelial and mesenchymal BMP signaling, showed highly increased formation of intestinal polyps morphologically similar to those in JP (Haramis et al, 2004;He et al, 2004). Loss of mesenchymal BMP signaling by conditional inactivation of BMPRII in stroma led to intestinal bleeding, thickness of mucosa due to epithelial hyperplasia and myofibroblast increment and multiple hemartomatous polyp appearance (Beppu et al, 2008;Hardwick et al, 2008). These expression patterns found in human polyposis syndromes indicate that altered BMP expression plays an important role in uncontrolled cell proliferation and tumorigenesis in the intestine.…”
Section: Bmp and Their Pathway In Other Gastrointestinal Diseasesmentioning
confidence: 99%
“…(Ishiguro et al, 2006). Important signalling pathways that are frequently disrupted in CRC, such as the transforming growth factor (TGF)-b (Naber et al, 2008), bone morphogenic protein (BMP; Hardwick et al, 2008) and Wnt pathway (Macheda and Stacker, 2008), play a role in both the cancer-associated stromal and epithelial compartment in the development of CRC. The presence of fibroblasts , myofibroblasts and endothelial cells (Baeten et al, 2006) in the cancer-associated stroma contributes to progression of CRC and a worse patient prognosis.…”
Section: Relation Between Total Epithelial and Stromal Apoptosis Andmentioning
confidence: 99%
“…In adult mice, BMPs have been shown to play critical roles in regulating the proliferation and differentiation of tissue stem cells, including neural and mesenchymal stem cells [11][12][13]. The tight regulation of BMPSmad1/5/8 signaling is physiologically important: dysregulation of this signaling has been found to result in tumor formation and the development of bone and vascular diseases [6,7,[14][15][16]. BMP-Smad1 signaling inhibits tumorigenesis via the prominent tumor-suppressive Atm-p53 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Smad1/5/8 activation is regulated by the inhibitory Smads, Smad6 and Smad7, dephosphorylation by protein phosphatases, such as PPM1A, and increased degradation by Smurf1 and Smurf2 [21][22][23][24][25]. Nuclear proteins, such as Sno and Ski, also inhibit the transactivation activity of Smad proteins via direct binding [14]. Some of the negative regulators, such as Smad6 and Smad7, are direct target genes of BMPSmad1/5/8 signaling, thus they form a negative feedback regulation loop.…”
Section: Introductionmentioning
confidence: 99%